Les modes de raisonnement informel des élèves de lycée lors de prises de décision en classe sur une question socio-scientifique - Elie Rached (Recherches en Éducation)
Our research describes higher secondary students’ informal reasoning during a classroom decision-making on a socio-scientific issue. Specifically, we examine students’ choices, their information preferences and their informal reasoning modes. 30 students (16-17 years’ old) responded to a survey presented to them before (pre-test) and after (post-test) an instruction on a socio-scientific issue regarding energy decision, choosing a heating system for a residency, in the context of global warming debates. Results indicate that students use mainly social information and a combined social-scientific informal reasoning mode. While no straight relation was found between heating system choices and informal reasoning modes. However, students with scientific and social informal reasoning modes tended to change their reasoning mode in the posttest more than students with a combined (scientific and social) informal reasoning mode.